Trem-2 Promotes Emergence of Restorative Macrophages and Endothelial Cells During Recovery From Hepatic Tissue Damage - Coelho, Inês; Duarte, Nádia; Barros, André; Macedo, Maria Paula; Penha-Gonçalves, Carlos (Frontiers in Immunology, 2021)
Upon hepatic injury macrophages are pivotal in mounting liver inflammatory and tissue repair reactions showing remarkable functional plasticity. Nevertheless, the molecular mechanisms determining macrophage transition from inflammatory to restorative phenotypes in the damaged liver remain unclear. Using mouse models of acute (APAP) or chronic (CCl4) drug-induced hepatotoxic injury we show that the immune receptor Trem-2 controls phenotypic shifts in liver macrophages and impacts endothelial cell differentiation during tissue recovery. Trem-2 gene ablation led to delayed re-population of Kupffer cells correlating with deterred resolution of hepatic damage following acute and chronic injury. We found that during tissue recovery macrophages in transition to the Kupffer cell compartment expressed high levels of Trem-2. Acquisition of the transition phenotype was associated with an unique transcriptomic profile denoting strong responsiveness to oxidative stress and downmodulation of the pro-inflammatory phenotype, which was not observed in absence of Trem-2. During tissue recovery lack of Trem-2 favored accumulation of a liver-damage associated endothelial cell population (LDECs) engaged in a transcriptional program compatible with endothelial de-differentiation. Accordingly, LDECs precursor potential is supported by the downregulation of surface endothelial cell markers and striking in vitro morphological changes towards typical endothelial cells. In conclusion, we found that the dynamics of liver macrophages in response to liver injury is critically controlled by Trem-2 and is interlinked with the de-differentiation of endothelial cells and heightened liver pathology. We propose that Trem-2 promotes the transition from the pro-inflammatory to the tissue repair phase by driving the acquisition of restorative properties of phagocytic macrophages.